ANALISIS PUTUSAN PENGADILAN TATA USAHA NEGARA SAMARINDA DALAM SENGKETA PERTANAHAN DITINJAU DARI UNSUR KTUN (Studi Kasus Putusan Nomor: 27/G/2020/PTUN.SMD) - Amus, Mico Kurnia; Kotijah, Siti; Paselle, Ennos (AL WASATH Jurnal Ilmu Hukum, 2024)
The article discusses the elements of KTUN (Keputusan Tata Usaha Negara) based on the Indonesian Law No. 5 of 1986 and Law No. 9 of 2004. KTUN is a written decision issued by a government agency or official that contains legal actions based on applicable laws and regulations, is concrete, individual, and final, and has legal consequences for individuals or legal entities. The article also presents a case study of a land dispute in Balikpapan, Indonesia, where the plaintiff filed a lawsuit under the Law No. 5 of 1986 to declare the disputed KTUN invalid. The defendant, the Head of the Balikpapan Land Office, issued a building permit that overlapped with the plaintiff's land ownership. The court ruled in favor of the plaintiff, declaring the defendant's building permit null and void and ordering the defendant to revoke it. The court's decision met all the elements of KTUN, including a written decision, issued by a government agency, based on applicable laws and regulations, concrete, individual, and final, and with legal consequences for the parties involved. The article emphasizes the importance of understanding the elements of KTUN, maintaining legal certainty, following applicable laws and regulations, respecting court decisions, and submitting lawsuits appropriately. The article concludes that the court's decision in the Balikpapan land dispute case is an example of how element of KTUN can facilitate the settlement of disputes and ensure legal certainty.